Optical properties of CdO films prepared by DC planar magnetron sputtering - Aadim, Kadhim Abdulwahid (University of Thi-Qar Journal of Science, 2014)
CdO films have been produced on glass substrates by DC planar magnetron sputtering technique in Ar and O2 gases 1:4 and distance 6cm between cathode and anode and thickness 174 nm. It is observed from optical properties that the films possess transmittance 80% in visible and near infrared region of spectrum and direct band gap values in the rang 2.31-2.4 e V.